Non-destructive techniques on zirconium alloy E110 with chromium coatings for the production of emergency-resistant core components of nuclear reactors; Перспективные материалы конструкционного и функционального назначения - Salman A. M. (Модификация поверхности, 2024)
This study evaluates the effectiveness of chromium coatings on zirconium alloy E110 in nuclear reactor core components. Various NDT methods were used to assess structural soundness and effectiveness. Results showed that increasing the chromium coating thickness improves electrical conductivity and thermoelectric properties, making it suitable for nuclear reactor applications. This enhances the long-lastingness and dependability of zirconium alloy components